EFFECTS OF CUSTOMER CARE ON ORGANIZATIONAL PERFORMANCE OF TELECOMMUNICATION COMMPANIES IN MOGADISHO-SOMALIA - ABDULLAHI ADEN, ABDULKADIR; Gichinga, Dr Lucy (IJRDO - Journal of Business Management, 2016)
The purpose of this research was to examine the effect of customer care on organizational performance. The study adopted a quantitative research with the specific research design being a descriptive design. The population of the study will be classified telecommunication companies located in Mogadishu; the sampling technique used will be purposive sampling. Primary data will be collected by use of questionnaires which were administered through drop and pick method. Data screening will be done to identify any missing data and will be further tested for reliability and normality. Data will be analyzed using SPSS version 22. The study found that service quality, customer satisfaction, customer relationship management, customer service delivery have significant and positive effects on organizational performance, Stepwise regressions revealed that customer care is determinants of organizational performance including service quality, customer satisfaction, customer relationship management, customer service delivery explained statistically significant portion of the variance associated with the extent of organizational performance of the telecommunication companies in Mogadishu-Somalia. he study recommended that there is need for the telecommunication companies in Mogadishu to increase their customer service delivery, service quality, customer satisfaction and customer relationship management as it was founded that these variables positively affects the organizational performance of telecommunication companies in Mogadishu.